Analysis Of Digital Marketing, Brand Awareness, Brand Image, And Price On Students' Decisions Studying At Panca Budi Development University - M. Ghazali Prasetyo; Hidayati Purnama Lubis; Fitra Arlina Nasution (Jurnal Fokus Manajemen, 2026)
The abstract is written in several sections described below, a maximum of 250 words in This study aims to analyze the influence of digital marketing, brand awareness, brand image, and price on students' decisions to study at Panca Budi Development University (UNPAB). The research approach used in this study is associative and quantitative. The population in this study were students of the Management Study Program at UNPAB with a sample of 100 respondents, determined using a saturated sampling technique. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression analysis with the help of the SPSS application. The results of the study indicate that partially digital marketing and brand image do not have a significant effect on students' decisions. In contrast, brand awareness and price have a positive and significant effect on students' decisions in choosing to study at UNPAB. Meanwhile, simultaneously digital marketing, brand awareness, brand image, and price have a significant effect on students' decisions. The coefficient of determination (R²) value of 0.404 indicates that the four independent variables are able to explain 40.4% of the variation in student decisions, while the remaining 59.6% is influenced by other factors outside the research model. The results of this study indicate that students' decisions in choosing a university are based more on rational considerations, especially regarding the level of brand awareness and the perception of price that corresponds to the benefits obtained, rather than simply digital information and brand image.